Genomic characterization of a carbapenem-resistant Citrobacter freundii clinical isolate from China carrying blaNDM-5 on a novel IncC-IncFIB-IncX3 plasmid - Hao Guo; Lirong Li; Yawen Zhang; Fang He (Journal of Global Antimicrobial Resistance, 2024)
ABSTRACT: Objectives: Citrobacter freundii is one of the important pathogens that can cause nosocomial infections. The advent of carbapenem-resistant C. freundii complicates clinical treatment. Here, we reported the genome sequence of a carbapenem-resistant C. freundii strain carrying a novel IncC-IncFIB-IncX3 plasmid in China. Methods: The genome sequence of C. freundii CRNMS1 was obtained using the Illumina NovaSeq 6000 platform and the long-read Nanopore sequencer. Multilocus sequence typing was identified using MLST (v.2.23.0). The identification of antimicrobial resistance genes (ARGs) and plasmid replicons was performed using the resfinder and plasmidfinder of ABRicate (v.1.0.1). Circular comparisons of plasmids were performed using the BLAST Ring Image Generator (BRIG). Results: CRNMS1 belongs to ST116 in the C. freundii MLST scheme. Thirteen ARGs were predicted in all, including blaNDM-5, which was located in a plasmid. The plasmid pblaNDM5-S1, which carried the blaNDM-5 gene, was discovered to be a novel plasmid including three plasmid replicons (IncC, IncFIB, and IncX3) as well as seven ARGs (sul1, sul2, floR, dfrA17, aadA5, qnrA1, and blaNDM-5). A total of 38 blaNDM-5-bearing C. freundii strains can be retrieved from the NCBI database. Phylogenetic analysis revealed a worldwide distribution of C. freundii strains carrying the blaNDM-5 gene, with China having the highest prevalence (39%, 15/38). However, they were distantly related to CRNMS1 with SNP differences >2545. Conclusion: In summary, we reported a novel IncC-IncFIB-IncX3 plasmid carrying blaNDM-5 in a carbapenem-resistant C. freundii strain in China. The development of such hybrid plasmids facilitates the transmission of ARGs.